The Main Problems of Engineering Training - Abdamitovich, Bayzakov Abdzhalil; A. A., Bayzakov (European Journal of Life Safety and Stability (2660-9630), 2021)
The construction industry and its further development in our country demonstrates a lack of competitive qualified engineers and builders in this field, which requires the development of fundamentally new approaches in the system of training personnel with the necessary higher education. This article deals with the problems of training construction professionals in higher education and improving the quality of education.